Living issues in philosophy - Harold H. Titus (Wadsworth, 1995)
Used by more than one million students around the world since its original publication, this introductory philosophy text makes accessible a wide range of philosophical issues closely related to everyday life. Emphasizing personal and immediate questions, the authors approach introductory philosophy through basic human questions rather than focusing on methodology or the history of thought. The text presents vital questions of contemporary interest in an overall framework of enduring concepts, interweaving coverage of various topics in art, history, and education. It covers a variety of types of philosophy in depth, and both western and eastern perspectives are represented. Ideal for students who have no background in philosophy, Living Issues in Philosophy, 9/e simplifies technical language wherever possible; unfamiliar terms are clearly defined upon first appearance and in the end-of-chapter glossaries. Additional pedagogical features include exercises, chapter summaries, and annotated bibliographies at the end of every chapter. The text also features photo biographies of major philosophers and short excerpts from philosophical classics